Specific heat capacity of pure triglycerides by differential scanning calorimeter - Morad, Noor Azian; Abu Hasan, Adilah (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
This report discusses the methods of measuring specific heat capacity of triglycerides using differential scanning calorimeter, DSC. The optimum operating conditions for specific heat capacity determination of triglycerides using the heat flux differential scanning calorimeter, is first established. Operating, conditions such as scanning rate, sample weight and atmospheric condition seemed to affect the specific heat capacity value considerably. The specific heat capacity of pure triglycerides are then determine using these optimum operating conditions. The pure triglycerides used in the experiment are four simple triglycerides and three mixed triglycerides. The four simple triglycerides used are trilaurin, trimyristin, tripalmitin and tristearin. The mixed triglycerides used are 1,2-dimyristoyl-3-oleoyl, 1,2-dimyristol-3-palmitoyl and 1,2- dioleoyl-3-palmitoyl. Comparisons of the specific heat capacity results are made with the reported values and values calculated for triglycerides using estimation methods. The accuracy of the specific heat capacity results for trglycerides are within 95% using DSC methods.